Investigation of agar as a soil analogue for corrosion studies. Issue 1 (11th April 2015) - Spark, A. J.; Cole, I.; Law, D.; Marney, D.; Ward, L.
Abstract : Solid agar based gels have been investigated as an electrolyte system for the electrochemical study of soil corrosion, specifically microbiologically influenced corrosion (MIC) in soil. Traditional techniques for studying corrosion in soil include solutions and soil samples; however these systems do not reliably simulate the physico‐chemical properties of soil. Soils are complex environments with three phases critical to corrosion (solid‐soil, liquid‐water and gas‐oxygen). Therefore there is a need for a system which replicates and considers this complex environment and its effects on corrosion processes, while reducing inconsistencies and variations associated with moisture and oxygen content in soil. Open circuit potential (OCP) and potentiodynamic scans (PDS) were conducted on carbon steel exposed to solid agar electrolyte with varying oxygen concentrations. Results were analysed using Tafel extrapolation, consistency in anodic‐cathodic trends and optical microscopy of the exposed regions. For the conditions tested, a cathodic shift was seen with the observed corrosion potentials being notably lower than the measured OCPs. Consistency in the anodic‐cathodic trends of the PDS was observed with minimal oxygen conditions. Overall, an agar based gel system has potential as an electrolyte for soil based MIC studies, especially as an analogue for moist clay soils.